2014
DOI: 10.4103/0301-4738.133521
|View full text |Cite
|
Sign up to set email alerts
|

Encephalocraniocutaneous lipomatosis: A case report and review of the literature

Abstract: Encephalocraniocutaneous lipomatosis (ECCL) is a rare, sporadic congenital neurocutaneous disorder that characteristically involves ectomesodermal tissues, such as skin, eyes, and central nervous system. A 3-day-old girl presented with swelling in her right eye since birth. Ocular examination of the right eye showed hypertrophy of bulbar conjunctiva with limbal dermoid, clouding of cornea, and atypical upper eyelid coloboma. The left eye showed conjunctival congestion and corneal vascularization. Dermatologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 11 publications
2
12
0
1
Order By: Relevance
“…Nevus psiloliparus and choristomas are observed in up to 80% of ECCL patients, whereas skin tags are another common sign that can be identified in up to 70% of cases (Moog, ). Optic nerve coloboma, identified in the right eye of our ECCL patient (#6), has been previously reported in at least two subjects with the disease (Chandravanhi, ; Hunter, ). Somatic FGFR1 and KRAS mutations were recently demonstrated in subjects with ECCL (Bennett et al, ; Boppudi et al, ).…”
Section: Discussionsupporting
confidence: 68%
“…Nevus psiloliparus and choristomas are observed in up to 80% of ECCL patients, whereas skin tags are another common sign that can be identified in up to 70% of cases (Moog, ). Optic nerve coloboma, identified in the right eye of our ECCL patient (#6), has been previously reported in at least two subjects with the disease (Chandravanhi, ; Hunter, ). Somatic FGFR1 and KRAS mutations were recently demonstrated in subjects with ECCL (Bennett et al, ; Boppudi et al, ).…”
Section: Discussionsupporting
confidence: 68%
“…El tratamiento es sintomático, por lo que en caso de crisis convulsivas se pautarán fármacos antiepilép-ticos. Se puede recurrir al tratamiento estético quirúr-gico para las lesiones dérmicas u oculares 14 .…”
Section: Discussionunclassified
“…22 Other reported ocular findings are aniridia, microphthalmia, hyaloid vessels, dislocation of the lens capsule, clouding of the cornea, iris dysplasia, colobomas, ocular calcifications, and optic nerve pallor. 8,54 The ocular lesions are usually ipsilateral to cutaneous and neurological findings. In 2003, Almer et al reported a case of ECCL with bilateral aniridia.…”
Section: Ocular Findingsmentioning
confidence: 99%